Community Based Adaptation To Climate Change And Social Economic In Xe Champhone Wetland, Champhone District, Savannakhet Province - siharath, Phoummixay; Somchay Vilaychaleun; Khampasith Thammathevo; Keophousone Phonhalath; Soulyphan Kannitha; Chankhachone Sonemanivong; Keoduangchai Keokhamphui; Phaiphana Siharath (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2024)
Climate change is key significant factor that impacts on multi-dimensions, which is relevant to social economic development, livelihood and environment, hence, Community Based Adaptation (CBA) to climate change is a mechanism of adapting based on the existing practices, knowledge, policy and experiences of the rice farmers to sustain their lives on changing climate, the objective of the study is to assess the social economic and find the practice management of rice farmers to adapt during flood and drought seasons. Hence, according to the research finds that, majority of the rice farmers are experienced and learnt from the previous effect and adjust themselves by using knowledge skills, experiences to build the resilience for their rice and crop planting in order to prevent and avoid the damages from climate change within the wetland. Besides that, the local communities still utilize the existing potential natural based adaptation to be flexible sustainably their agricultural activities and livelihood during rainy and dry season